Husbandry and Sustainability of Water Buffaloes in Turkey - Orhan Ermetin (Turkish Journal of Agriculture: Food Science and Technology)
Water buffaloes in Turkey originate from Mediterranean Water Buffaloes, a subgroup of river water buffaloes and are known as Anatolian Water Buffalo. During the 1970’s the number of water buffaloes in Turkey was one million, but in 2010 this figure dropped to about 85.000. Thanks to the incentives introduced for water buffalo husbandry in recent years, the water buffalo population has risen to 143.073 heads. Water buffalo husbandry in Turkey is performed in some provinces of the Black Sea, Marmara and Central Anatolian Regions. The provinces with the highest amount of water buffalo existence are listed as Samsun, Diyarbakır, Istanbul, Tokat, Bitlis, Muş, Afyon, Kayseri, Sivas and Amasya. Breeding style in Turkey is in the form small family business, with an average of 1-5 animals per enterprise. Family enterprises are keeping water buffaloes for their own consumption. Mostly breeding in modern enterprises formed for indoor barn breeding, the size of the herds is around 50 to 100 heads. Being done only at swamps or waterfronts in the past, water buffalo husbandry increasingly takes place in modern facilities nowadays. The colour of Anatolian Water Buffaloes is generally black and their horns curved backwards, are called arch horns in Turkey. The lactation milk yield and lactation length in Anatolian Water Buffaloes are between 800 and 1100 kg and about 180-280 days respectively. It is demonstrated that they varied according to effects of environmental factors, care and feeding. Adult water buffalo’s live weight is about 411-518 kg. The first insemination age of water buffalo is 32 to 43 months and during a lifespan the number of lactation periods is 5 to 10. For adult water buffalo at withers the height of females is being expressed as around 135 cm. Calves are generally breastfed for 3-4 months. Generally, water buffaloes are milked twice a day in the village farms by hand.